Immunoglobulin M response in largemouth bass (Micropterus salmoides) following ranavirus infection - Zhenyu Huang; Naicheng Liu; Mingyang Xue; Chen Xu; Yuding Fan; Yan Meng; Nan Jiang; Yiqun Li; Wenzhi Liu; Yang He; Yong Zhou (Frontiers in Immunology)
Immunoglobulin M (IgM) and IgM+ B cells are key components of the humoral immune system, providing defense against pathogen invasion. While the role of IgM in the systemic and mucosal immune responses of fish to parasites and bacteria has been partially investigated, its function in viral infections remains underexplored. This study successfully developed a largemouth bass (Micropterus salmoides) model for ranavirus immersion infection. Our findings revealed that viral infection caused significant pathological changes in the gill and head kidney tissues, along with a marked upregulation of adaptive immune gene expression. Interestingly, fish that survived an initial viral infection exhibited minimal mortality and low viral loads in the gill and head kidney tissues when exposed to a higher viral concentration. Notably, in these fish with secondary infections, there was a significant increase in IgM protein levels in both the blood and gill mucus, as well as a pronounced accumulation of IgM+ B cells in the gill and head kidney tissues. Additionally, the serum contained high levels of virus-specific IgM, which demonstrated the ability to neutralize the virus. These findings highlight the crucial role of IgM in the immune response to viral infections in largemouth bass and suggest its potential as a target for enhancing viral resistance in aquaculture.